1988
DOI: 10.1111/j.1469-8986.1988.tb01902.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Lipid, Lipoprotein, Cardiovascular, and Neuroendocrine Responses to Acute Stress

Abstract: This study had two objectives: (a) to examine whether or not lipids and lipoproteins change in response to acute behavioral stress in young adults; and (b) to test the extent of sex differences in the magnitude of the lipid, lipoprotein, neuroendocrine, and cardiovascular changes during stress. Nineteen women and 22 men participated in a serial subtraction task, a videotaped speech task, and a self‐evaluation task. The cholesterol portions of low density and high density lipoproteins, triglycerides, free fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
113
8
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(131 citation statements)
references
References 46 publications
9
113
8
1
Order By: Relevance
“…However, findings are inconsistent with some studies suggesting elevations in blood lipids even after adjustment for changes in hemoconcentration [18,19].…”
Section: Introductioncontrasting
confidence: 58%
“…However, findings are inconsistent with some studies suggesting elevations in blood lipids even after adjustment for changes in hemoconcentration [18,19].…”
Section: Introductioncontrasting
confidence: 58%
“…If it were true that males experienced more stress-induced hypercholesterolemia during the entrance examination period and then decreased their serum total cholesterol levels to a greater extent than females, this result would be consistent with previous research which has shown that young adult men had greater total cholesterol changes during stress than young adult women. 36) However, the effect of gender on serum cholesterol is not conclusive because other researchers have indicated that the serum total cholesterol due to an examination stressor correlated positively with depression but that there were no significant gender differences in cholesterol response. 37) It is possible that a gender difference in the cholesterol response might be characteristic of a young, highly intelligent population.…”
Section: Discussionmentioning
confidence: 99%
“…As would be expected, they differed on screening SBP, F(1,20) = 50.97, p < .001, η 2 p = .718, and DBP, F(1,20) = 7.84, p = .01, η 2 p = .282. Women were excluded from the study for four reasons: their low prevalence of elevated resting blood pressure (Carroll et al, 1991); the possibility of variations in reactivity with menstrual cycle phase (Hastrup & Light, 1984;Stoney, Matthews, McDonald, & Johnson, 1988); the sensitivities involved in thoracic scanning; and our aim to replicate our previous study (Carroll et al, 2009). …”
Section: Participantsmentioning
confidence: 99%